2017
DOI: 10.1016/j.ecss.2017.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis of three dimensional flow models applied to tidal energy sites in Scotland

Abstract: Parametric analysis of three dimensional flow models applied to the tidal energy sites in ScotlandCitation for published version: Abdul rahman, A & Venugopal, V 2017, 'Parametric analysis of three dimensional flow models applied to the tidal energy sites in Scotland ' Estuarine, Coastal and Shelf Science, vol. 189, General rightsCopyright for the publications made accessible via the Edinburgh Research Explorer is retained by the author(s) and / or other copyright owners and it is a condition of accessing thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…Several previous studies have also carried out modeling using various tools, such as Delft3D [14], FVCOM (Finite Volume Coastal Ocean Model) [1], ROMS (Regional Ocean Model System) [4], and MIKE [6].…”
Section: Numerical Modelmentioning
confidence: 99%
“…Several previous studies have also carried out modeling using various tools, such as Delft3D [14], FVCOM (Finite Volume Coastal Ocean Model) [1], ROMS (Regional Ocean Model System) [4], and MIKE [6].…”
Section: Numerical Modelmentioning
confidence: 99%
“…Similar studies have been conducted using other software, such as Delft3D [9], Telemac [15], ROMS [10], FVCOM [4], and MIKE [16]. The current study uses MIKE 3 (personal license).…”
Section: Model Setupmentioning
confidence: 99%
“…Several studies have estimated that 25 % of tidal energy in Europe is in Scottish waters and the potential to generate electricity is greater than what is currently consumed [15]. Rahman and Venugopal [16] provided a detailed analysis of several input parameters of two different numerical models: Telemac3D and Delft3D which are used for the simulation of tidal current flow at potential tidal energy sites in the Pentland Firth in Scotland. The research results indicated that the Telemac3D and Delft3D models allowed an excellent comparison with the measured data, where Delft3D the model showed the highest correlation compared to the measured data.…”
Section: Introductionmentioning
confidence: 99%